Birth and Neonatal Transition in the Guinea Pig: Experimental Approaches to Prevent Preterm Birth and Protect the Premature Fetus - Hirst, Jonathan J.; Palliser, Hannah K.; Shaw, Julia C.; Crombie, Gabrielle; Walker, David W.; Zakar, Tamas (Frontiers in Physiology, 2018)
The guinea pig (Cavia porcellus) displays many features of gestational physiology that makes it the most translationally relevant rodent species. Progesterone production undergoes a luteal to placental shift as in human pregnancy with levels rising during gestation and with labor and delivery occurring without a precipitous decline in maternal progesterone levels. In contrast to other laboratory rodents, labor in guinea pigs is triggered by a functional progesterone withdrawal, which involves the loss of uterine sensitivity to progesterone like in women. In both species the amnion membrane is a major source of labour-inducing prostaglandins, which promote functional progesterone withdrawal by modifying myometrial progesterone receptor expression. These similar features appear to result from convergent evolution rather than closer evolutionally relationship to primates compared to other rodents. Nevertheless, the similarities in the production, metabolism and actions of progesterone and prostaglandins allow information gained in pregnant guinea pigs to be extended to pregnant women with confidence. This includes exploring the effects of pregnancy complications including growth restriction and the mechanisms by which stressful conditions increase the incidence of preterm labor. The relatively long gestation of the guinea pig and the maturity of the pups at birth particularly in brain development means that a greater proportion of brain development happens in utero. This allows adverse intrauterine conditions to make a sustained impact on the developing brain like in compromised human pregnancies. In addition, the brain is exposed to a protective neurosteroid environment in utero, which has been suggested to promote development in the guinea pig and the human. Moreover, in utero stresses that have been shown to adversely affect long term neurobehavioral outcomes in clinical studies, can be modelled successfully in guinea pigs. Overall, these parallels to the human have led to increasing interest in the guinea pig for translational studies of treatments and therapies that potentially improve outcomes following adverse events in pregnancy and after preterm birth.